2009
DOI: 10.2478/10004-1254-60-2009-1969
|View full text |Cite
|
Sign up to set email alerts
|

A Journey Through Mitogen-Activated Protein Kinase and Ochratoxin A Interactions

Abstract: A Journey Through Mitogen-Activated Protein Kinase and Ochratoxin A InteractionsOchratoxin A (OTA) is a ubiquitous mycotoxin with potential nephrotoxic, carcinogenic, and cytotoxic action. It has been proposed that OTA might be involved in the development of Balkan endemic nephropathy, which is associated with an increased risk of urinary tract tumours, and of other forms of interstitial nephritis. Cell susceptibility to OTA mainly depends on mycotoxin concentrations, duration of exposure, and intracellular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In summary, these studies showed that OTA is nephrotoxic, hepatotoxic, neurotoxic, teratogenic and immunotoxic in various animals and in vitro , with renal toxicity and carcinogenesis being the key adverse effects. Many studies of OTA from the last decade support a non-DNA-reactive genotoxic mechanism, which involves different epigenetic mechanisms mainly related to oxidative stress, compensatory cell proliferation and disruption of cell signaling and division, and these publications have been thoroughly reviewed by various authors [ 6 , 63 , 70 , 113 , 119 , 139 , 140 ]. However, a direct genotoxic mechanism involving OTA bioactivation and DNA adduct formation is also still discussed [ 115 , 120 ] and this mechanism is also consistent with some in vivo gene expressionresults [ 113 ].…”
Section: Differential Toxicity Of Ochratoxin Group Membersmentioning
confidence: 99%
“…In summary, these studies showed that OTA is nephrotoxic, hepatotoxic, neurotoxic, teratogenic and immunotoxic in various animals and in vitro , with renal toxicity and carcinogenesis being the key adverse effects. Many studies of OTA from the last decade support a non-DNA-reactive genotoxic mechanism, which involves different epigenetic mechanisms mainly related to oxidative stress, compensatory cell proliferation and disruption of cell signaling and division, and these publications have been thoroughly reviewed by various authors [ 6 , 63 , 70 , 113 , 119 , 139 , 140 ]. However, a direct genotoxic mechanism involving OTA bioactivation and DNA adduct formation is also still discussed [ 115 , 120 ] and this mechanism is also consistent with some in vivo gene expressionresults [ 113 ].…”
Section: Differential Toxicity Of Ochratoxin Group Membersmentioning
confidence: 99%
“…Furthermore, it has been reported that OTA might regulate cell fate via stimulating Mitogen Activated Protein Kinase (MAPK) family members, including ERK1/2, JNK, and p38 MAPK4111213. MAPKs are evolutionarily conserved serine/threonine kinases that respond to various chemical and physical stresses and play essential roles in cell survival and adaptation14.…”
mentioning
confidence: 99%
“…Moreover, it has been reported that mere activation of p38 and JNK may not be necessary for apoptosis under all conditions, but concurrent inhibition of ERK1/2 is also a critical factor [38]. Thus, a dynamic balance between ERK pathway and p38 and JNK pathways determines whether a cell will survive or undergo apoptosis [39] which has been observed to be shifting towards p38 and JNK, leading to apoptosis in mouse skin following dermal exposure to OTA.…”
Section: Discussionmentioning
confidence: 99%